Individualized care theory, measurement, research and practice - (:unkn) unknown (My University, 2018)
© Springer International Publishing AG, part of Springer Nature 2019. This contributed book is based on more than 20 years of researches on patient individuality, care and services of the continuously changing healthcare system. It describes how research results can be used to respond to challenges on individuality in healthcare systems. Service users’, patients’ or clients’ point of views on care and health services are urgently needed. This book describes the conceptualisation of the individualized nursing care phenomenon and the process development of the measuring instruments of that phenomenon in different contexts. It describes results from a variety of clinical contexts about individualized nursing care and explains factors associated with the perceptions and delivery of individualized nursing care from different point of views. This book may appeal to clinicians, nurses practitioners and researchers from many fields.
Keywords: Individuality; Nursing care; Nursing practice; Nursing science; Person-centeredness